VDT visual fatigue monitoring based on feature extraction from unconstrained BCG. Issue 23 (29th November 2019) - Jiang, Yongxiang; Wang, Peng; Sun, Guifen; Cao, Jinjing; Lin, Weimin; Zhou, Hongchao
Abstract : An unconstrained visual display terminal (VDT) visual fatigue monitoring method based on BCG is studied. A VDT visual fatigue test is designed and implemented in this study, also acceleration signals are obtained by using an acceleration sensor, which is installed on the seat back. Then, BCG is obtained by adaptive threshold wavelet denoising, FFT, frequency domain filtering in the range of heart rate, and IFFT. Low frequency (LF) is extracted after the RR interval and JJ interval are calculated by the wavelet algorithm. Curves of two kinds of LF with the usage of VDT were obtained and were identical. Thus, the authors can draw conclusions that BCG can replace ECG to achieve unconstrained monitoring of VDT visual fatigue and LF gradually increases with VDT visual fatigue becoming more and more serious. Finally, we compare LF curves of BCG and ECG during use VDT to draw a conclusion that BCG can replace ECG to monitor VDT visual fatigue in an unconstrained way. Also, the confidence interval is used to verify the reliability of SD subjective evaluation, and the conclusion is reliable.